2017
DOI: 10.1177/2041386617734299
|View full text |Cite
|
Sign up to set email alerts
|

Clinical conceptualization of workaholism

Abstract: Workaholism is a behavioral addiction that, while widely studied, is still lacking a definition shared by the scientific community. The aim of this theoretical paper is to propose a new model that is at the same time comprehensive and easy to test, with an approach based on a critical analysis of the literature. We give particular attention to reviews of literature and theoretical and empirical papers published since 2011, because even the most recent reviews do not fully encompass the last few years. We propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 80 publications
4
74
0
3
Order By: Relevance
“…We believe, in line with Kardefelt-Winther [22] and Loscalzo and Giannini [20], that we should go beyond a-priori assumptions of addiction when proposing a new potential behavioral addiction, as to identify the real manifestation of the problem behavior. We speculate that this could be suitable for workaholism too.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…We believe, in line with Kardefelt-Winther [22] and Loscalzo and Giannini [20], that we should go beyond a-priori assumptions of addiction when proposing a new potential behavioral addiction, as to identify the real manifestation of the problem behavior. We speculate that this could be suitable for workaholism too.…”
Section: Introductionmentioning
confidence: 61%
“…In line with this, a meta-analysis conducted in 2012 by Patel, Bowler, Bowler, and Methe [19] showed that the WorkBat and the WART have different correlations with the work-related variables they analyzed. Given these issues related to the lack of a shared definition, Loscalzo and Giannini [20] developed a theoretic model of workaholism that comprehends the three main components of this construct: externalizing symptoms (i.e., addiction symptoms), internalizing symptoms (i.e., obsessive-compulsive symptoms), and work engagement.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations